The Effect of STEM Integrated Guided inquiry Learning Model on Problem solving Skills of Grade 8 Students on Vibration Material and Waves - Wijayanti, Rr. Galih Mega; Setiawan, Agung Mulyo (Jurnal Pendidikan MIPA, 2025)
In the 21st century, students are required to possess problem-solving skills, this is because students' problem-solving skills are closely related to real-life issues. However, in reality, students' problem-solving abilities in Indonesia are still very low. This has been demonstrated by research conducted by PISA and TIMSS. The primary objective of this study is to evaluate the impact of implementing a guided inquiry learning model integrated with STEM on problem-solving skills, specifically in the subject of vibrations and waves. This study uses a quasi-experimental pretest-posttest design with a control group to test the effectiveness of the intervention. The study involved two classes with different treatments as samples: the control class, which did not receive the intervention, and the experimental class, which receive the intervention, with 30 students in each class. Data analysis testing was conducted using the Shapiro-Wilk normality test, homogeneity test, independent sample t-test, and N-Gain test. The research data analysis revealed an improvement in problem-solving skills in the theory of vibrations and waves through the application of the guided inquiry model integrated with STEM. This is evident based on the independent sample t-test with a Sig.value is 0.000 (p < 0.005), leading to the conclusion that the guided inquiry learning model integrated with STEM significantly affects the problem-solving abilities of 8th-grade students in the topic of vibrations and waves.     Keywords: guided inquiry, STEM, problem solving skills, vibration and wave.